Asymmetric Aziridination of Chalcone Promoted by Binaphthalene-Based Chiral Amines - Page, Philip C. Bulman; Bordogna, Céline; Strutt, Ian; Chan, Yohan; Buckley, Benjamin R. (Synlett, 2013)
Aminimines derived in situ from a number of enantiomerically pure binaphthalene-based tertiary amines have been used for the asymmetric aziridination of chalcone, providing N-unprotected aziridines with ee values of up to 43%. A chiral hydrazinium salt has been isolated for the first time and shown to provide similar yield and enantioselectivity to the in situ process in reaction with chalcone.
Keywords: chalcone; aziridination; binaphthalene-based tertiary amines